Taking Out TB–Lysosomal Trafficking and Mycobactericidal Ubiquitin-Derived Peptides - Purdy, Georgiana (Frontiers in Microbiology, 2011)
Tuberculosis remains a significant global health concern. The hallmark of Mycobacterium tuberculosis pathogenicity is its ability to infect resting macrophages and establish an intracellular niche. Activated and autophagic macrophages control mycobacterial infections through bactericidal mechanisms ranging from reactive oxygen and nitrogen intermediates to the delivery of the bacterium to the acidified, hydrolytically active lysosome. The mycobactericidal activity of the lysosome is due in part to the action of ubiquitin-derived peptides (Ub-peptides). In this review we discuss the trafficking events that result in delivery M. tuberculosis to the lysosome, the source and lysosomal generation of Ub-peptides and their role in macrophage control of M. tuberculosis infection.